Analisis Kurikulum PAUD di Kabupaten Rejang Lebong dan Relevansinya Terhadap Kurikulum Prodi PIAUD IAIN Curup - Siti Zulaiha; Baryanto Baryanto (Institut Agama Islam Negeri (IAIN) Curup, 2019)
This research is motivated by the importance of conducting an analysis related to the implementation of the curriculum in PAUD in Rejang Lebong Regency, this is because the curriculum that is applied is not uniform along with the changes in existing regulations. In addition, it is based on the importance of analyzing the relevance of the PIAUD Study Program curriculum with the applicable curriculum in PAUD so that it can be an improvement in the future. The purpose of this study is to describe how the curriculum concept, analyze the implementation of the curriculum describes the relevance of the Early Childhood Education curriculum in Rejang Lebong District to the Curriculum for Early Childhood Islamic Education Study Program. This study is a field research that is descriptive qualitative in nature. Data sources or informants are the Head and Teacher of Early Childhood Education. Data collection techniques used are interview, observation and documentation. Data analysis begins by reducing the data that has been collected, then presented in the form of a description of the data and the final conclusion from the results and analysis that has been done. The results of this study indicate that: first, the content of the PAUD curriculum in Rejang Lebong Regency which refers to the 58 of 2009 includes PAI, Language, Cognitive, Physical, Akhlakul Karimah, Independence, Emotional Social. Whereas those referring to Ministerial Regulation 2014 of 2014 are aspects of the development of Religious and Moral Values, Motoric, Cognitive, Emotional, Language and Art. Secondly, the implementation of the PAUD curriculum in Rejang Lebong Regency in general has been in accordance with the applicable curriculum guidelines but only in teaching and learning activities that many have not used the learning model that should be applied, then the approach has not been implicitly included in the daily work plan prepared by the teacher. Third, the relevance of the PAUD curriculum to the PIAUD Study Program curriculum in general has been relevant, but the content and placement of the components of the offered courses and their extent and depth need to be reviewed.